S11 Inappropriate prescribing of combination inhalers in asthma in Northern Ireland (NI). (2nd December 2011) - Sweeney, J; Marley, A M; Patterson, C; Heaney, L G
Abstract : Introduction: BTS/SIGN asthma management guidelines recommend a stepwise approach to the use of anti-inflammatory therapy, including the addition of inhaled combination therapy (ICT) at Step 3. In NI, ICT accounts for 47% (£23 million) of the entire respiratory drug spend suggesting excessive utilisation of ICT. Methods: Using data from a large representative sample of GP practices in NI, we looked at subjects who had a new prescription of ICT (Symbicort, Seretide, Fostair). Data were collected from the Information and Registration Unit of the Business Services Organisation for the period January to December 2010 inclusive for subjects aged 5 to 35. We examined treatment prior to ICT, SABA, oral steroid and antibiotic use and, prescription filling in the preceding 6 and 12 months. Results: 42 665 subjects received 2 or more prescriptions for any respiratory drug (BNF categories 3.1, 3.2, 3.3) and of these 12 989 received ICT with 3953 new ICT prescriptions. 2642 (67%) of these had no ICS in study year or 6 month lead in period. A further analysis of a 12-month lead in period showed 39 315 subjects with 2 or more respiratory prescriptions and out of these 11 962 received ICT with 2609 new ICT prescriptions. 1359 (52%) had no ICS in the study year or 12-month lead in. A sub-group analysis (n=600) showed that 51% of first prescriptions for ICT are made in Jan–April but in the previous 6 months only 23% are issued a SABA, 5% receive OCS and 31% receive an antibiotic. Conclusion: ICT is initiated in the majority of young asthmatic subjects without prior inhaled steroid therapy. Most prescriptions are initiated in the January–April period and do not appear to be driven by severe asthma exacerbation (oral steroid prescription) or worsening asthma control (SABA use). Significant reductions in ICT, with associated cost savings, would occur if the BTS/SIGN prescribing guidelines were followed in primary care. We are currently trying to identify the drivers and potential economic impact of poor adherence to national prescribing guidelines and examine ICT prescribing in other UK regions to identify if this is a more widespread problem.